Studi Ekonomi Digital Di Indonesia - Teguh Permana; Andriani Puspitaningsih (Universitas Nusantara PGRI Kediri, 2021)
This study aims to determine the development of the digital economy in Indonesia. The research method used is descriptive method with content analysis or content analysis. Broadly speaking, this writing systematic is more of a narrative nature that collects the opinions of experts, journals, books and articles published on the internet related to the development of the digital economy in Indonesia. The results show that the digital economy continues to develop and is even predicted to increase eight times and it is projected that the value of Indonesia's digital economy in 2024 will reach 1796 trillion rupiah. The implication of this is that the government must be fast in building its supporting infrastructure so that it can go faster.